I really want to make lemonade! - Ziefert, Harriet (Ziefert, Harriet. Really Bird story, 2023)
"Really Bird is a small bird who lives in a large city park. Today he is thinking ... I really want to make lemonade! But it will take working together to make a unique refreshing drink."--Page 4 of cover